2016
DOI: 10.1371/journal.pone.0146689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organic Carbon Electron Donors on Microbial Community Development under Iron- and Sulfate-Reducing Conditions

Abstract: Although iron- and sulfate-reducing bacteria in subsurface environments have crucial roles in biogeochemical cycling of C, Fe, and S, how specific electron donors impact the compositional structure and activity of native iron- and/or sulfate-reducing communities is largely unknown. To understand this better, we created bicarbonate-buffered batch systems in duplicate with three different electron donors (acetate, lactate, or glucose) paired with ferrihydrite and sulfate as the electron acceptors and inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 76 publications
4
26
0
Order By: Relevance
“…The presence of specific electron donors has been shown to have significant impacts on the development of microbial communities and the formation of Fe(II)-bearing minerals in laboratory based-experiments and in-situ studies in subsurface environments [52,53,[93][94][95][96]. Likewise, in this study we observe that specific electrons donors lead to the formation specific Fe(II)-bearing secondary minerals during DIR of lepidocrocite by S. putrefaciens CN32.…”
Section: Fe(ii) Secondary Mineral Formationsupporting
confidence: 66%
“…The presence of specific electron donors has been shown to have significant impacts on the development of microbial communities and the formation of Fe(II)-bearing minerals in laboratory based-experiments and in-situ studies in subsurface environments [52,53,[93][94][95][96]. Likewise, in this study we observe that specific electrons donors lead to the formation specific Fe(II)-bearing secondary minerals during DIR of lepidocrocite by S. putrefaciens CN32.…”
Section: Fe(ii) Secondary Mineral Formationsupporting
confidence: 66%
“…However, the rarefaction curves indicated that species richness was generally higher in samples from the carcass burial site than in those from the manure heap ( S2 Fig ). These results suggested that the anoxic and anaerobic conditions and the leachate chemical compositions (e.g., various organic acids) at the carcass burial site might have created metabolic complexities that supported an increase in bacterial diversity [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flexible metabolisms have been observed in many Fe(III)‐reducing bacteria, which consolidates adaptation to environmental fluctuations of electron donors and acceptors (Melton et al ., ) and the bacterial community patterns in Fe(III)‐bioreduction environments have been well documented (Weber et al ., ; Cardenas et al ., ; Kwon et al ., ). In a recent study, acetate addition as electron donor specifically promoted Proteobacteria and Firmicutes as Fe(III) reducers in the system (Kwon et al ., ). Cardenas and colleagues () observed more Delta‐ and Beta‐Proteobacteria in the acetate‐treated zones than in the background area.…”
Section: Discussionmentioning
confidence: 97%